INTERIOR IDEAL FUZZY SEMIRING - Saman Abdurrahman (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2021)
Semiring is one of the ring extensions, which eliminates the inverse axiom in the first operation. One of the topics on the semiring is the ideal interior. This study introduces the concept of the ideal interior semiring and the ideal interior fuzzy semiring. Further, it examined the properties of the ideal fuzzy semiring interior and the nature of the existence of the ideal interior semiring if the ideal fuzzy interior is given.